Relation between u-learning, connective learning, and standard xAPI: A systematic review - Ramirez, Gabriel M. (2018)
U-Learning is the educational process that is performed at any time, place, context and through any device. It is the application of omnipresence in education. The paper presents a systematic review of U-Learning related to the xAPI standard and connective learning. In the systematic review, 824 articles were found in 6 academic databases. According to the inclusion criteria, 54 papers were selected. This paper aims to find links between connective learning and the xAPI standard in the framework of U-Learning.